Membrane-Based Electrochemical Detection of Uranium: A Review - Jingyue Zhang; Qing He; Wen Zhang (Separations, 2022)
The determination of uranium in environmental samples has always been a crucial environmental issue due to its adverse impacts on human life. Electrochemical detection is one of the most suitable methods for directly determining uranium because of its portable instrument and quick response characteristics. The ion-selective membrane in the working electrodes is selectively responsible for uranium transport and separation. This mini-review provides a general overview of the membrane-based ion-selective electrodes in detecting uranium ions reported in the literature. The ion-selective membranes are classified according to their ionophore categories. Furthermore, the limits and outlook are also discussed to provide a reference for further developing membrane-based electrochemical uranium sensors.